Emotional Intelligence And Behavioral Bias On Stock Trading Decisions In Robo Advisor Moderation In The Millennial Generation - Rahman, Arista Widya; Puspita, Nindi Vaulia (Universitas Nusantara PGRI Kediri, 2024)
Research aim : To understand the investment behavior of the millennial generation in the Indonesian stock market with a focus on the relationship between Emotional Intelligence (EI), behavioral bias, and stock trading decisions. Design/Methode/Approach : Using a quantitative descriptive approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data was collected through an online survey targeting 100 millennials. Research Finding : Emotional Intelligence and Behavioral Bias positively influence Stock Trading Decisions. Robo Advisor also has a positive impact. Theoretical contribution/Originality : This research presents a new contribution by delving into the complex interaction between EI, behavioral bias, and the moderating impact of Robo Advisor on stock trading decisions for the millennial generation. Practitionel/Policy implication : Practical recommendations are provided for market players, robo advisors, and millennials. Policy implications relate to understanding and implementing adaptive investment solutions Research limitation : Sample limitations, external factors, and advantages/disadvantages of the PLS-SEM method